Understanding autism [ parents, doctors, and the history of a disorder - Silverman, Chloe (Princeton, New Jersey : Princeton University Press, 2012)
Tracks developments in autism theory and practice over the years. This title shows how an understanding of autism has been constituted and stabilized through vital efforts of schools, gene banks, professional associations, government committees, parent networks, and treatment conferences
1. Research programs, "autistic disturbances," and human difference -- 2. Love is not enough : Bruno Bettelheim, infantile autism, and psychoanalytic childhoods -- 3. Expert amateurs : raising and treating children with autism -- 4. Brains, pedigrees, and promises : lessons from the politics of autism genetics -- 5. Desperate and rational : parents and professionals in autism research -- 6. Pandora's box : immunizations, parental obligations, and toxic facts
Includes bibliographical references (p. 313-327) and index
Keywords: Autism in children; Autism in children -- Treatment; Autistic children -- Family relationships; Parents of autistic children